2002
DOI: 10.1086/340450
|View full text |Cite
|
Sign up to set email alerts
|

Germline Alterations of the RNASEL Gene, a Candidate HPC1 Gene at 1q25, in Patients and Families with Prostate Cancer

Abstract: The RNASEL gene (2',5'-oligoisoadenylate-synthetase dependent) encodes a ribonuclease that mediates the antiviral and apoptotic activities of interferons. The RNASEL gene maps to the hereditary-prostate-cancer (HPC)-predisposition locus at 1q24-q25 (HPC1) and was recently shown to harbor truncating mutations in two families with linkage to HPC1. Here, we screened for RNASEL germline mutations in 66 Finnish patients with HPC, and we determined the frequency of the changes in the index patients from 116 families… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
182
5
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(201 citation statements)
references
References 15 publications
13
182
5
1
Order By: Relevance
“…Truncating mutation E265X was reported to cosegregate in highrisk US families with hereditary prostate cancer . E265X was also associated with hereditary prostate cancer in Finnish patients (Rökman et al, 2002). In the present study, E265X mutation was not observed in cases and controls.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Truncating mutation E265X was reported to cosegregate in highrisk US families with hereditary prostate cancer . E265X was also associated with hereditary prostate cancer in Finnish patients (Rökman et al, 2002). In the present study, E265X mutation was not observed in cases and controls.…”
Section: Discussioncontrasting
confidence: 55%
“…In Finnish patients, the truncation mutation at base pair position 793 (Glu265-stop) was associated with hereditary prostate cancer (Rökman et al, 2002). Wang et al (2002) reported the association of the Arg462Gln genotype with familial prostate cancer risk in a United States population.…”
mentioning
confidence: 99%
“…However, specific evidence of a role for RNase L in the suppression of cancer had to wait almost 10 years, until the long sought, hereditary prostate cancer 1 (HPC1) was mapped to the RNase L gene by the group of Jeff Trent [92]. Several germline mutations or variants in HPC1/RNASEL have been observed in hereditary prostate cancer [92][93][94][95] (reviewed in ref. [96]), including a common (35% allelic frequency) missense variant of RNase L, in which a G to A transition at nucleotide position 1385 (G1385A) results in a glutamine instead of arginine at amino acid position 462 (R462Q).…”
Section: The Role Of Rnase L In Hereditary Prostate Cancer and Discovmentioning
confidence: 99%
“…The RNase L "Q" variant had a 3-fold decrease in catalytic activity compared to the wild-type enzyme [95,97]. Although several genetic and epidemiologic studies support the involvement of RNASEL (and notably the R462Q variant) in prostate cancer etiology [92][93][94][95], others did not [98][99][100], suggesting that either population differences or environmental factors such as infections may modulate the impact of RNASEL on prostatic carcinogenesis.…”
Section: The Role Of Rnase L In Hereditary Prostate Cancer and Discovmentioning
confidence: 99%
“…So far, only two genes have been identified from these chromosomal regions: ELAC2 from HPC2 -locus (Tavtigian et al, 2001) and RNASEL (MIM 180435) from HPC1 -locus . In Finland neither ELAC2 nor RNASEL did explain the disease segregation in HPC families, but seemed to have some kind of modifying role in prostate carcinogenesis (Rokman et al, 2001;Rokman et al, 2002). Xu et al (2001) identified a new locus at 8p22 -23, and mutations in MSR1 gene (MIM 153622) were reported to associate with prostate cancer .…”
mentioning
confidence: 99%